2022
DOI: 10.1101/2022.11.01.514742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated Multi-Omics Analysis of Brain Aging in Female Nonhuman Primates Reveals Altered Signaling Pathways Relevant to Age-Related Disorders

Abstract: The prefrontal cortex (PFC) is central to working memory, temporal processing, decision making, flexibility, and goal-oriented behavior, and has been implicated as a key brain region responsible for age-related cognitive decline. Although studies in humans and multiple nonhuman primate (NHP) species have shown reduction of PFC activity associated with cognitive decline, little is known about aging-related molecular changes in PFC that may mediate these effects. To date, no studies have used untargeted discover… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The direction of E/I changes may vary depending on the brain area studied. In the prefrontal cortex, available experimental data support an increase in inhibition with age, correlating with memory de cits (Potier et al, 2006;Stanley et al, 2012;Bories et al, 2013;Bañuelos et al, 2014;Cox et al, 2023), while evidence of decreased inhibition was found in the sensory systems and hippocampus (Yu, Wang et al, 2006). In the rat parietal cortex, an imbalance of arousal/inhibition in favor of inhibition correlated with cognitive impairment (Wong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The direction of E/I changes may vary depending on the brain area studied. In the prefrontal cortex, available experimental data support an increase in inhibition with age, correlating with memory de cits (Potier et al, 2006;Stanley et al, 2012;Bories et al, 2013;Bañuelos et al, 2014;Cox et al, 2023), while evidence of decreased inhibition was found in the sensory systems and hippocampus (Yu, Wang et al, 2006). In the rat parietal cortex, an imbalance of arousal/inhibition in favor of inhibition correlated with cognitive impairment (Wong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%